2003
DOI: 10.1107/s1600536803006457
|View full text |Cite
|
Sign up to set email alerts
|

(m-Carboxyphenyl)ammonium perchlorate at 223 K

Abstract: Key indicatorsSingle-crystal X-ray study T = 223 K Mean '(C±C) = 0.003 A Ê R factor = 0.036 wR factor = 0.140 Data-to-parameter ratio = 11.8For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 7 publications
4
10
0
Order By: Relevance
“…The mean deviation of the ammonium exocyclic group from the least-squares plane of the phenyl ring is very small [À0.0178 (9) Å ] and corresponds to a (1 ) out-of-plane bending of the C4-N1 bond. The ammonium NH þ 3 group is slightly staggered from the plane of the benzene ring; this staggered conformation was found in a number of mcarboxyphenylammonium salts (Benali-Cherif et al, 2002;Bendjeddou et al, 2003) and it appears to be preferred over the eclipsed conformation observed previously in mcarboxyphenylammonium bisulfate (Cherouana et al, 2003). The geometrical features of the m-carboxyphenylammonium cations are also in accordance with other similar compounds (see, for example, Arora et al, 1973).…”
Section: Figuresupporting
confidence: 79%
“…The mean deviation of the ammonium exocyclic group from the least-squares plane of the phenyl ring is very small [À0.0178 (9) Å ] and corresponds to a (1 ) out-of-plane bending of the C4-N1 bond. The ammonium NH þ 3 group is slightly staggered from the plane of the benzene ring; this staggered conformation was found in a number of mcarboxyphenylammonium salts (Benali-Cherif et al, 2002;Bendjeddou et al, 2003) and it appears to be preferred over the eclipsed conformation observed previously in mcarboxyphenylammonium bisulfate (Cherouana et al, 2003). The geometrical features of the m-carboxyphenylammonium cations are also in accordance with other similar compounds (see, for example, Arora et al, 1973).…”
Section: Figuresupporting
confidence: 79%
“…All other refinement details are available in the CIF (CCDC: 1401464). (2) 8.2058 (12) 114.691 (19) 2323.6(6) The Valance bond sum (1.995 A°) [30][31][32] confirms that the nickel ion in our complex is as A°and 109.47° (17), respectively, confirming a tetrahedral configuration (Table 3 and 4), similar to other perchlorates studied at low temperature) [37][38][39].…”
Section: Structuresupporting
confidence: 59%
“…The asymmetric unit, formed by one Mn 2+ metal ion, two crystallographically independent oxime ligands and two perchlorate counter-ion located on general positions. The molecular structure of the compound showing the atom numbering scheme is shown in Figure. 1 (17), respectively, confirming a tetrahedral configuration , similar to other perchlorates studied at low temperature) [20,[22][23][24].…”
Section: Structuresupporting
confidence: 55%